Changing survival of people with myeloma and end stage kidney disease: A cohort study using Australian and New Zealand dialysis and transplant registry 1963–2013. Issue 3 (20th February 2018) - Webster, Angela C; Irish, Ashley B; Kelly, Patrick J
Abstract: Background: It is unclear whether recent advances in myeloma therapy have improved survival for all those with myeloma and end stage kidney disease (ESKD). Methods: Population‐based registry cohort study using Australia and New Zealand Dialysis and Transplant Registry data 1963–2013. We measured survival of people with myeloma and other plasma cell dyscrasias and ESKD over time, and investigated prognostic factors for improved survival using survival analysis (results expressed as hazard ratios (HR) with 95% confidence intervals). Results: We included 65 940 people (207 595 person‐years); 1067 people (1.6%) with myeloma and 572 (0.9%) with other plasma cell dyscrasia. Myeloma ESKD rose from 0.8% before 1994 to 2.2% in 2004 and remained stable. People with myeloma were older, and age increased over time, from 62.5 before 1994 to 70.1 years from 2010, but the non‐myeloma group age increased more steeply (52.0 before 1994; 62.2 from 2010). In myeloma patients, survival improved ( P < 0.001) with recent predicted 5 year survival of 27.5% aged <55, 32.2% aged 55–64, 16.3% for 65–74 and 12.7% aged ≥75 years. Survival did not improve for plasma cell dyscrasia patients ( P = 0.70). Myeloma patients on peritoneal dialysis had improved survival compared with those on haemodialysis (HR 0.7, CI 0.6–0.9), but those aged ≥65 had poorer survival (65–74 years HR 1.5, CI1.2–1.9; ≥75 HR 1.7, CI1.3–2.1), as did diabetics (HR 1.3, CI1.1–1.6). Conclusions: The proportion of people with myeloma and ESKD remains stable, but their survival has progressively improved in Australia and New Zealand. On starting ESKD treatment with myeloma, a 59 year old without diabetes on peritoneal dialysis can expect a 45% 5 year survival, where a 75‐year‐old diabetic on haemodialysis has 9% 5 year survival. Summary at a Glance: Using the ANZDATA, this study documents improvements in survival of patients with end stage kidney failure from myeloma or other plasma cell dyscrasias after commencing dialysis. It also examines factors associated with survival on dialysis and provides important information that can help clinicians advise their patients with this rare cause of end stage kidney failure on their expected survival after commencing dialysis.